The Impact of Peer Review on Creative Self-efficacy and Learning Performance in Web 2.0 Learning Activities - Liu, Chen-Chung; Lu, Kuan-Hsien; Wu, Leon Yufeng; Tsai, Chin-Chung (Educational Technology ＆ Society, 2016)
Many studies have pointed out the significant contrast between the creative nature of Web 2.0 learning activities and the structured learning in school. This study proposes an approach to leveraging Web 2.0 learning activities and classroom teaching to help students develop both specific knowledge and creativity based on Csikzentmihalyi's system model of creativity. The approach considers peer review as the core component in the Web 2.0 learning activities with the aim of engaging students in the creative learning paradigm. To gain a better understanding of the impact of such an approach on students' confidence and performance, this study gathered and analyzed the works developed by 53 sixth graders in a Web 2.0 storytelling activity, as well as details of their creative self-efficacy. The results show that those students who experienced the peer review using a set of storytelling rubrics produced significantly more sophisticated stories than those who did not. Furthermore, the peer review did not exert a significant negative influence on the students' creative self-efficacy. It was also found that the experimental group's (students experiencing the peer review) creative self-efficacy consistently reflected their performance, while the control group's creative self-efficacy did not. Such results support that the peer review process may help students to build a sophisticated level of reflection upon their creative work in Web 2.0 learning activities.